InP DHBT technology for power amplifiers at mm-wave frequencies. (September 2017) - Midili, V.; Nodjiadjim, V.; Johansen, T.K.; Squartecchia, M.; Riet, M.; Dupuy, J.Y.; Konczykowska, A.
Abstract: An InP Double Heterojunction Bipolar Transistor (DHBT) technology is presented for millimeter-wave power amplifiers at E-band and higher frequencies. Single- and multi-finger transistors with 0.7 μ m emitter width and emitter lengths of 5, 7, 10 μ m are designed for high frequency and high power applications. The static and AC performances of the fabricated devices are discussed. Reported cutoff frequency and maximum oscillation frequency are f t = 267 GHz and f max = 450 GHz for a 0.7 × 5 μ m P 2 single-finger device, respectively. Results from large-signal measurements at 30 GHz are reported for single and 4-finger devices. Ballasted devices are introduced to improve thermal behaviour and to increase the limits of the safe operating area (SOA). The SOA is improved approximately by 75% for 4-finger devices with 0.7 × 10 μ m 2 emitter. A fabricated monolithic microwave integrated circuit (MMIC) at E-band based on stacked InP DHBTs is presented and its performances reported to demonstrate the power capabilities of the technology.